COMPARISON OF THE MEANING OF “LOSS” IN BISHOP’S “ONE ART” (1976) AND JUNAEDHIE’S POEM “TAK ADA YANG HILANG” (2009): DERRIDA’S PERSPECTIVE OF DECONSTRUCTION - Raissabita, Nadia Ukhi; Santoso, Heri Dwi; Prihantono, Kahar Dwi (Lire Journal (Journal of Linguistics and Literature), 2025)
Loss is a universal experience, yet its interpretation varies across cultures. This study aims to provide a comparative analysis of the meaning of loss in Elizabeth Bishop’s poem “One Art” (1976) and Kurniawan Junaedhie’s poem “Tak Ada Yang Hilang” (2009) using Jacques Derrida’s perspective of deconstruction. This study explores how these poems reflect and deconstruct the meaning of loss through logocentrism, binary opposition, and difference. The findings indicate that while Bishop presents loss as an art to be mastered, reflecting Western pragmatism and individualism, Junaedhie portrays loss as a transformation rather than an absence, rooted in Eastern perspectives on continuity and presence. This research contributes to the field of comparative literature and poetry analysis by highlighting the cultural and philosophical dimensions of loss.